Unveiling the intellectual structure of informality : insights from the socioeconomic literature (2024)
In the socioeconomic sphere, the concept of informality has been used to address issues pertaining to economic dynamics, institutions, work, poverty, settlements, the use of space, development, and sustainability, among others. This thematic range has giv